Penerapan Metode UCD (User Centered Design) dalam Pengembangan dan Implementasi Pengelolaan Sistem Magang Online - Mia Nurhaliza; Ardian Firosha; Deddy Prayama; Taufik Gusman (JITSI : Jurnal Ilmiah Teknologi Sistem Informasi, 2026)
Internships are a mandatory activity for students at several universities, especially vocational colleges and vocational high school students, as a graduation requirement. They aim to apply the knowledge gained during their studies in the workplace. However, the management of prospective intern registration and management services is still done manually, resulting in inefficiency and the potential for administrative errors. Therefore, digitizing the internship registration and management process is necessary to improve the efficiency of the registration process and data management of prospective interns. This study aims to design a website-based online internship management system that can simplify administration, minimize errors, and all needs and activities through this website such as registration, attendance, daily logbooks, uploading final internship reports and awarding certificates upon completion of the internship. For the Agency, this system will simplify data management and increase transparency in internship management. Related research shows that the online internship management system is effective in accelerating the online registration and monitoring process for interns. The User-Centered Design method was chosen as the approach in designing this system, focusing on user needs through the stages of analysis, design, development, and evaluation of the system in an iterative manner. The developed system will be tested using usability testing to assess the level of ease of use and user satisfaction. By implementing this method, it is hoped that the online internship management system will be more efficient and transparent, as well as improve the internship registration and management process, making it more organized and modern